Strategi Produk Hospital At Home Sebagai Inovasi Layanan Masa Depan - Rohadi Rohadi; Wachyu Sulistiadi (LPPM Universitas Respati Indonesia, 2026)
Introduction: Overcrowding in hospital inpatient facilities has become a major challenge that can reduce service quality, operational efficiency, and patient safety. Advances in healthcare technology, along with the growing demand for more personalized care, have encouraged the emergence of the Hospital at Home (HaH) concept as an alternative home-based inpatient care model. This study aims to analyze the product development strategy of Hospital at Home through the integration of homecare services and remote monitoring technology. Methods: This study employed a qualitative approach using a literature review method. Data were collected from scientific articles, academic journals, and other relevant literature related to the implementation of Hospital at Home. Results: The findings indicate that Hospital at Home is effective for patients with stable acute conditions who meet specific clinical criteria. This model can reduce hospital inpatient burdens, improve patient comfort, and lower healthcare service costs. Its successful implementation depends on the readiness of multidisciplinary teams, integrated homecare systems, and reliable remote monitoring technologies. Conclusion: Hospital at Home represents an innovative healthcare service model with the potential to enhance service quality, hospital efficiency, and patient satisfaction in a sustainable manner.Keywords: Hospital at Home; Overcrowding; Integrated homecare; Remote monitoring; Service innovation.